Is type 2 diabetes associated dementia a microvascular early-Alzheimer’s phenotype induced by aberrations in the peripheral metabolism of lipoprotein-amyloid? - Takechi, Ryusuke; Sharif, Arazu; Brook, Emily; Majimbi, Maimuna; Chan, Dick C.; Lam, Virginie; Watts, Gerald F.; Mamo, John C. L. (Frontiers in Endocrinology, 2023)
There is increasing evidence of a positive association of type 2 diabetes with Alzheimer’s disease (AD), the most prevalent form of dementia. Suggested pathways include cerebral vascular dysfunction; central insulin resistance, or exaggerated brain abundance of potentially cytotoxic amyloid-β (Aβ), a hallmark feature of AD. However, contemporary studies find that Aβ is secreted in the periphery by lipogenic organs and secreted as nascent triglyceride-rich lipoproteins (TRL’s). Pre-clinical models show that exaggerated abundance in blood of TRL-Aβ compromises blood-brain barrier (BBB) integrity, resulting in extravasation of the TRL-Aβ moiety to brain parenchyme, neurovascular inflammation and neuronal degeneration concomitant with cognitive decline. Inhibiting secretion of TRL-Aβ by peripheral lipogenic organs attenuates the early-AD phenotype indicated in animal models, consistent with causality. Poorly controlled type 2 diabetes commonly features hypertriglyceridemia because of exaggerated TRL secretion and reduced rates of catabolism. Alzheimer’s in diabetes may therefore be a consequence of heightened abundance in blood of lipoprotein-Aβ and accelerated breakdown of the BBB. This review reconciles the prevailing dogma of amyloid associated cytotoxicity as a primary risk factor in late-onset AD, with substantial evidence of a microvascular axis for dementia-in-diabetes. Consideration of potentially relevant pharmacotherapies to treat insulin resistance, dyslipidaemia and by extension plasma amyloidemia in type 2 diabetes are discussed.